(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Bio Medical Waste management has been receiving highest priority in hospitals after the act was introduced by the Ministry of Environment and Forest, titled Bio Medical Waste Management and Handling Rules 1998. About 0.33 million tons of waste is generate per annum in India. Hospital acquired infections are on the rise due to improper waste management practice. A cross sectional, longitudinal study on Bio Medical waste management practice in a mortuary and casualty was conducted at a tertiary care teaching hospital from 1st July 2018 to 31st December 2018. The study focused on knowledge and practice of waste management in the casualty and mortuary. Interestingly, the practice of Bio Medical waste management was excellent in casualty and mortuary. Awareness of the hazards of improper waste management was poor among sanitary workers whereas doctors, nurses and other paramedical staff were well aware of the hazards.